2001
DOI: 10.1034/j.1399-5448.2001.20402.x
|View full text |Cite
|
Sign up to set email alerts
|

Varying clinical presentations at onset of type 1 diabetes mellitus in children - epidemiological evidence for different subtypes of the disease?

Abstract: Although the symptoms of diabetes at its onset follow a uniform pattern, the clinical presentation and duration of symptoms indicate that there may be various forms of type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
6
28
0
2
Order By: Relevance
“…4,6-8, [12][13][14]23 Although others have reported that a positive family history of T1D is associated with the earlier recognition of symptoms of newonset diabetes, 7 we did not find a correlation between a history of T1D in a first-degree family member and early recognition of symptomatic hyperglycemia in children under age 6 years.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…4,6-8, [12][13][14]23 Although others have reported that a positive family history of T1D is associated with the earlier recognition of symptoms of newonset diabetes, 7 we did not find a correlation between a history of T1D in a first-degree family member and early recognition of symptomatic hyperglycemia in children under age 6 years.…”
Section: Discussionmentioning
confidence: 51%
“…One possible explanation for this difference is that we have studied an age-restricted group, whereas other investigators have compared children under age 5 years to children 5 years and older. 9,11,14 An alternative explanation is that younger children do not have a shorter period of inadequate insulin secretion but do have a more severe metabolic decompensation at diagnosis. Our data support this explanation because we found no correlation between age and HbA1c across a 6-year age span, although we identified an age-related inverse correlation with tCO 2 at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] It remains unknown why some children present in DKA and whether the development of diabetic ketoacidosis is a consequence of delayed diagnosis and treatment or whether it reflects a particularly aggressive form of diabetes. 10 In our study, 39.7% and 37.9% of patients suffered from moderate and severe DKA, respectively. Other studies reported that mild DKA was more frequent than moderate and severe.…”
Section: Discussionsupporting
confidence: 46%
“…In Germany till now no studies exist about the frequency of these diseases. Studies about the frequency of diseases, like the one about diabetes mellitus type 1 [8,25,26] are of considerable interest for the health-care system. They establish the conditions to plan the logistics of paediatric endocrinology and diabetology in Germany.…”
Section: Introductionmentioning
confidence: 99%